2018
DOI: 10.1038/s41598-018-23919-w
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging including semiquantitative short-wavelength and near-infrared autofluorescence in achromatopsia

Abstract: Multimodal imaging provides insights into phenotype and disease progression in inherited retinal disorders. Congenital achromatopsia (ACHM), a cone dysfunction syndrome, has been long considered a stable condition, but recent evidence suggests structural progression. With gene replacement strategies under development for ACHM, there is a critical need for imaging biomarkers to define progression patterns and follow therapy. Using semiquantitative plots, near-infrared (NIR-AF) and short-wavelength autofluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Previously, we have reported similar BCVA between eyes in CNGA3-ACHM (n = 31). 16 Matet et al 39 also reported a strong correlation between interocular visual acuities. Our study further supports visual functional symmetry, with similar BCVA, CS, MS, V TOT , and V 5 between eyes.…”
Section: Discussionmentioning
confidence: 91%
“…Previously, we have reported similar BCVA between eyes in CNGA3-ACHM (n = 31). 16 Matet et al 39 also reported a strong correlation between interocular visual acuities. Our study further supports visual functional symmetry, with similar BCVA, CS, MS, V TOT , and V 5 between eyes.…”
Section: Discussionmentioning
confidence: 91%
“…However, the clinical significance of FAF in ACHM remains poorly established, and we would predict that any progression in this parameter is likely to be slow and small in magnitude. Interestingly, recent work by Matet et al 15 has advocated the role of near-infrared autofluorescence (NIR-AF) in the investigation of ACHM. While the Spectralis device performs short-wavelength autofluorescence (SW-AF) imaging, NIR-AF is a less frequently used imaging modality.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sundaram et al 12 and Langlo et al 8 reported symmetry in the grade of the ellipsoid zone disruption on OCT (using this fact to support a study design in which they conducted more detailed analyses in just one eye of each subject). In addition, Matet et al 31 found no interocular difference in the size of ellipsoid zone defect on OCT. Mastey et al 11 also demonstrated no significant difference in foveal ONL thickness in 76 subjects with ACHM (though the ONL thickness was generally reduced compared to control subjects). In addition, Matet et al 31 showed no difference between eyes in the extent of the hyperautofluorescent perifoveal ring observed using short-wavelength autofluorescence or the extent of the central hypoautofluorescence observed using near-infrared autofluorescence.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…In addition, Matet et al 31 found no interocular difference in the size of ellipsoid zone defect on OCT. Mastey et al 11 also demonstrated no significant difference in foveal ONL thickness in 76 subjects with ACHM (though the ONL thickness was generally reduced compared to control subjects). In addition, Matet et al 31 showed no difference between eyes in the extent of the hyperautofluorescent perifoveal ring observed using short-wavelength autofluorescence or the extent of the central hypoautofluorescence observed using near-infrared autofluorescence. Aboshiha et al 17 also reported no difference in fundus autofluorescence between eyes in a cohort of 38 patients with ACHM.…”
Section: Accepted Manuscriptmentioning
confidence: 95%